Granulomertic classification of bottom sediments of small rivers of the northern Azov Sea region - Berozkina, Liudmyla (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Introduction. Grain size is a key characteristic in the study of bottom sediments. There are a large number of approaches to the classification of granulometric composition, but most of them were created for sedimentary rocks or soils, not sediments, so arises a problem of choosing an appropriate methodology for describing bottom sediments. The most common among researchers of bottom sediments is the Folk classification and its modifications. This approach is used by Geological Surveys of the USA and the countries of European Union for seabed mapping and research of bottom sediments. Therefore, to characterize the bottom sediments of the northern Sea of Azov region, a simplified Folk classification was used. It consists of eleven classes and is represented through a three-term dependence. The generalized scheme consist of four classes. Methods. Granulometric analysis was conducted by dry sieve method. Results were grouped according to two classification schemas (by Frolov and by Folk). Graphics were made with the Python programming language, libraries Matplotlib and MplTern. Results and Discussions. Grain size distribution was calculated for 39 samples of bottom sediments from rivers the Obytichna, the Solona, the Mokra Bilosaraika, the Komyshuvatka, underwater discharge cone of the temporary steam in Petrivska ravine and from beach zone between cities Prymorsk and Berdyansk. Years of sampling 2017, 2018, 2021. A comparison is made of the traditional for Ukrainian lithological studies division into psephites, psamites, siltstones, and pelites with the division into sediment granulometric aggregates (gravel, sand, mud) according to the Folk scheme. Psephites is equal to gravel, pelites is equal to mud. Sand consist of psamites and siltstones. Folk’s approach allows not only to demonstrate the percentage content of a certain group, but also to attribute the bottom sediment to a certain class based on its ratio. According to Folk’s triangle: all samples from the Mokra Bilosaraika river are sandy gravel; bottom sediments of the Komyshuvatka are gravelly sand; the Obytichna river – three samples of gravelly sand and two samples of sandy gravel; the Solona river – tree gravelly sand, one sand and one gravelly muddy sand; samples from underwater discharge cone are mostly gravelly sand, but two of them sandy gravel and one is sand; coastline samples are five gravelly sand, five gravelly muddy sand, three sand and two muddy sand. If classified according to a generalized scheme, the vast majority of the studied material is coarse sediments, with a small amount of mixed, sandy sediments and occasional samples of mud with muddy sand. Conclusions. The studied sediments are predominantly coarse-grained sandy material. If we take into account only the results of granulometric analysis, they indicate the following sedimentation processes: the material is poorly transported, the forces of material transfer are insufficient for its crushing and compaction, the material is mobile, unsorted and poorly accumulated - it is constantly eroded and redeposited. Modern lithological studies in Ukraine require structured recommendations for the interpretation and presentation of results, approval of translations of terms borrowed from English-language literature for the purpose of integration into the European scientific community.